NILAI KERUGIAN DAN MITIGASI KONFLIK MONYET EKOR PANJANG (Macaca fascicularis) DAN BERUK (Macaca namestrina) DI SEKITAR SUAKA MARGASATWA BUKIT RIMBANG BUKIT BALING - Gusnaini, Nurmutia; Yoza, Defri; Darlis, Viny Volcherina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
ABSTRACT Utilization of the area by human needs has resulted in a narrowing of the habitat of long-tailed monkeys and monkeys which has triggered human and wildlife conflicts such as in Petai Village and Pulau Padang Village which are around the Bukit Rimbang Bukit Baling Wildlife Reserve. This conflict between humans and wildlife has a negative impact, both in the form of a decrease in the population of long-tailed monkeys and monkeys in their natural habitat as well as in the form of economic losses for the community. Such conditions require the calculation of the economic value due to human and wildlife conflicts as part of the consideration in obtaining efforts to resolve the conflict. This study aims to determine the prevention efforts of long-tailed monkey andmonkey conflicts with humans and to determine the value of losses due to disturbance of long-tailed monkeys and monkeys in Petai Village and Pulau Padang Village. This study uses purposive sampling method, using the Slovin formula as many as 74 respondents. Methods of data analysis using descriptive analysis to determine conflict mitigation techniques for long-tailed and monkey monkeys and quantitative analysis to be used to calculate the value of human losses and conflicts with long-tailed and monkey monkeys, namely the value of agricultural damage losses in rupiah units. Damage to agricultural commodities in Petai Village and Padang Island, namely oil palm, rubber, banana, papaya, chilli, eggplant, long beans and cassava. The results of the calculation of the average damage in Petai Village / one attack obtained a value of Rp. 1,786,413 per household, while in Pulau Padang village the average calculation of damage / attack was Rp. 2,645,009 per household. Efforts to control conflict by the community are in the form of guarding and controlling the gardens, making barriers in the form of installing wire fences and evictions.Keywords :Conflict, Long Tailed Monkey, monkey, Mitigation, Damage Costs, wildlife.